Is insulin the most effective injectable antihyperglycaemic therapy?. Issue 2 (9th November 2014) - Buse, J. B.; Peters, A.; Russell‐Jones, D.; Furber, S.; Donsmark, M.; Han, J.; MacConell, L.; Maggs, D.; Diamant, M.
<x xml:space="preserve">Abstract</x> Aims The recent type 2 diabetes American Diabetes Association/European Association for the Study of Diabetes (ADA/EASD) position statement suggested insulin is the most effective glucose‐lowering therapy, especially when glycated haemoglobin (HbA1c) is very high. However, randomized studies comparing glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) exenatide once‐weekly [OW; DURATION‐3 (Diabetes therapy Utilization: Researching changes in A1c, weight, and other factors Through Intervention with exenatide ONce‐Weekly)] and liraglutide once‐daily [OD; LEAD‐5 (Liraglutide Effect and Action in Diabetes)] with insulin glargine documented greater HbA1c reduction with GLP‐1RAs, from baseline HbA1c ∼8.3% (67 mmol/mol). This post hoc analysis of DURATION‐3 and LEAD‐5 examined changes in HbA1c, fasting glucose and weight with exenatide OW or liraglutide and glargine, by baseline HbA1c quartile. Methods Descriptive statistics were provided for change in HbA1c, fasting glucose, weight, and insulin dose, and subjects (%) achieving HbA1c <7.0%, by baseline HbA1c quartile. Inferential statistical analysis on the effect of baseline HbA1c quartile was performed for change in HbA1c. An analysis of covariance (ANCOVA) model was used to evaluate similarity in change in HbA1c across HbA1c quartiles. Results At 26 weeks, in both studies, HbA1c reduction, and proportion of subjects reaching HbA1c <7.0%, were similar or numerically greater with the GLP‐1RAs than glargine for all baseline HbA1c quartiles. Fasting glucose reduction was similar or numerically greater with glargine. Weight decreased with both GLP‐1RAs across all quartiles; subjects taking glargine gained weight, more at higher baseline HbA1c. Adverse events were uncommon although gastrointestinal events occurred more frequently with GLP‐1RAs. Conclusions HbA1c reduction with the GLP‐1RAs appears at least equivalent to that with basal insulin, irrespective of baseline HbA1c. This suggests that liraglutide and exenatide OW may be appropriate alternatives to basal insulin in type 2 diabetes, including when baseline HbA1c is very high (≥9.0%).